Analyzing job entry examinations for Mathematics teachers of Colegio Pedro II during the 19th Century Analisando provas de concursos para professores de Matemática no Colégio Pedro II no século XIX - Flávia Soares (Universidade Estadual Paulista, 2010)
In a attempt to investigate historic aspects of mathematics teaching, we ask what kind of instruments can be used to rebuild the professional trajectory of teachers and their practices, and what elements can be used to analyze the issues related to promotion of mathematics teacher in Brazil. One of these elements is public teacher job entry examinations. The analysis of these exams can show what were the requirements to work as a teacher and to clear other important questions about the conception about teachers at that time, about the contents they should teach, and others. This paper emphasizes the contents of the exams, and the formal requirements and abilities measured in those exams to act as a mathematics teacher in an important secondary education institution in the 19th Century, Colégio Pedro II. Keywords: Public contest. Mathematics teachers. Century XIX. Colégio Pedro II. Na tentativa de investigar aspectos históricos do ensino de Matemática, questionam-se que tipos de instrumentos podem ser utilizados para reconstruir a trajetória profissional do professor e de suas práticas e a partir de quais elementos pode-se examinar de maneira mais rigorosa as questões relativas ao acesso à profissão de professor de Matemática no Brasil. Um desses elementos são as provas de concursos. A análise dessas provas é capaz de revelar quais as exigências para o exercício do magistério e trazer à tona questões importantes a respeito da concepção da época em relação ao papel do professor, aos conteúdos que deveria ensinar, entre outros aspectos. Este trabalho enfatiza o conteúdo das provas, as exigências formais e as habilidades medidas nos exames para os cargos de professor de Matemática da principal instituição de ensino secundário do Brasil no século XIX, o Colégio Pedro II. Palavras-chave: Concursos. Professor de Matemática. Século XIX. Colégio Pedro II.